2020
DOI: 10.1136/bmjsrh-2019-200509
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and HIV acquisition among women: an updated systematic review

Abstract: ObjectiveTo update a 2016 systematic review on hormonal contraception use and HIV acquisition.MethodsWe searched Pubmed and Embase between 15 January 2016 and 26 June 2019 for longitudinal studies comparing incident HIV infection among women using a hormonal contraceptive method and either non-users or users of another specific hormonal contraceptive method. We extracted information from newly identified studies, assessed study quality, and updated forest plots and meta-analyses.ResultsIn addition to 31 previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Omics analyses of human mucosal samples have suggested DMPA may alter vaginal epithelial repair pathways at a molecular level, which may impact epithelial permeability [ 29 , 30 ]. While observational studies have linked DMPA usage with increased HIV acquisition risk in women [ 31 33 ], the Evidence for Contraceptive Options and HIV Outcomes trial was designed to better assess this question, and showed no significant increase in HIV acquisition risk between DMPA, copper IUD, and LNG implant [ 34 ]. While the ECHO trial supported the safety profile of DMPA, interactions between hormonal contraceptives and mucosal immunology are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Omics analyses of human mucosal samples have suggested DMPA may alter vaginal epithelial repair pathways at a molecular level, which may impact epithelial permeability [ 29 , 30 ]. While observational studies have linked DMPA usage with increased HIV acquisition risk in women [ 31 33 ], the Evidence for Contraceptive Options and HIV Outcomes trial was designed to better assess this question, and showed no significant increase in HIV acquisition risk between DMPA, copper IUD, and LNG implant [ 34 ]. While the ECHO trial supported the safety profile of DMPA, interactions between hormonal contraceptives and mucosal immunology are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…All authors screened abstracts and full-text articles using Covidence,6 and conflicts were resolved through discussion. Two authors (KC and AT) also screened all the articles included in a companion review of hormonal contraceptive use and risk of HIV acquisition7 to identify any additional studies that included an IUD-only arm.…”
Section: Methodsmentioning
confidence: 99%
“…Prof Hallett reports grants USAID and the Bill and Melinda Gates Foundation during the conduct of the study; grants from BMGF, World Bank, UNAIDS, Rush Foundation and Wellcome Trust; and personal fees from BMGF, New York University, WHO and GFATM outside the submitted work. Office of AIDS and TB Research, South African Medical Research Council, Pretoria, South Africa; 3 USAID, Pretoria, South Africa; 4 National Department of Health, Pretoria, South Africa; 5 Botswana Harvard AIDS Institute, Gaborone, Botswana; 6 Liverpool School of Tropical Medicine, Liverpool, United Kingdom; Parktown, South Africa; 9 UNAIDS Eastern and Southern Africa, Johannesburg, South Africa…”
Section: O M P E T I N G I N T E R E S T Smentioning
confidence: 99%